Elementary particle physics - Kenyon I R (London Rutledge and Kegan Paul Ltd., 2023)
Introduction; Leptons quarks and forces; Experimental techniques; QED and the gauge principle; Symmetrics and conservations laws; Color and QCD; The V-A theory of weak; Electroweak unification; Electroweak probs and hadron.
Keywords: Particle Physics